Move : how decisive leaders execute strategy despite obstacles, setbacks, and stalls - Azzarello, Patty (John Wiley & Sons, Inc., 2017)
Your guide to mobilizing your whole organization to take your business forward, this practical book identifies the chronic challenges that keep organizations from decisively executing strategy, and gives you a practical game plan for breaking through. --